2020
DOI: 10.3390/nu12051371
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effects of Eating Disorder, Food Addiction, and Insomnia in the Association between Psychological Distress and Being Overweight among Iranian Adolescents

Abstract: With obesity and excess weight remaining a serious concern worldwide, investigating the mechanisms underlying this is of great importance. Psychological distress is a possible trigger contributing to excess weight for adolescents. Moreover, the association between psychological distress and excess weight may be mediated by eating disorder, food addiction, and insomnia. The present study utilized parallel mediation analysis to assess the aforementioned associations and possible mediation effects among Iranian a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 53 publications
0
26
0
1
Order By: Relevance
“…Kappa for the abstract review was 0.88 (95% CI; 0.77–0.98), and Kappa for the full text review was 0.92 (95% CI; 0.84–0.99). All 22 studies were cross‐sectional 24,28–48 . No longitudinal studies were identified in the search.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Kappa for the abstract review was 0.88 (95% CI; 0.77–0.98), and Kappa for the full text review was 0.92 (95% CI; 0.84–0.99). All 22 studies were cross‐sectional 24,28–48 . No longitudinal studies were identified in the search.…”
Section: Resultsmentioning
confidence: 99%
“…Prevalence of FA as determined using the YFAS‐C has been reported in 18 publications 24,28–32,34–39,41,42,45–48 (Table 2). The meta‐analysis estimated an overall FA prevalence at 15% (95% CI: 11–19%) among children and adolescents, with an I 2 of 95.64%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…That is, if body image issues and anxiety have an adverse impact on weight gain among adolescents, the association could be via the mediation effect of eating behaviors. 33 Understanding these risk factors for disordered eating behavior in an obesogenic context is imperative in the weight management context.…”
Section: Discussionmentioning
confidence: 99%